2020
DOI: 10.1039/d0cp03086d
|View full text |Cite
|
Sign up to set email alerts
|

Ground state of the Fe(ii)-porphyrin model system corresponds to quintet: a DFT and DMRG-based tailored CC study

Abstract: Fe(II)-porphyrins play an important role in many reactions relevant to material science and biological processes, due to their closely lying spin states. Although the prevalent opinion is that these systems...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 53 publications
7
25
0
Order By: Relevance
“…In the present study, we were interested solely in the scaling characteristics of our parallel scheme, we therefore do not present any energies (they would be out of context anyway). Nevertheless, the detailed study of the Fe(II)‐porphyrin model was already published elsewhere 62 and chemistry‐oriented articles about the remaining two systems should also appear soon.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we were interested solely in the scaling characteristics of our parallel scheme, we therefore do not present any energies (they would be out of context anyway). Nevertheless, the detailed study of the Fe(II)‐porphyrin model was already published elsewhere 62 and chemistry‐oriented articles about the remaining two systems should also appear soon.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the MPS matrices are nothing, but reshaped renormalization matrices ), and they are easily obtainable from the DMRG sweep algorithm 43 . They can be used for example, for efficient calculations of correlation functions or a subset of the FCI expansion coefficients, which may be employed for the purposes of the tailored coupled cluster methods 39,58–62 . If we reshape Olp1s,lpL ) to Llp1,lps(i.e., 4 M × M matrix into M × M × 4 tensor) and similarly for the right block matrix, then starting with the wave function expansion in the renormalized basis ) and recursive application of ) would lead to |ΨMPS=sLs1Ls2ψsisi+1Rsn.|s1s2sn which is the two‐site MPS form of the DMRG wave function.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…38 For comparison with the SC-NEVPT2 results, we employed the small complete active space (CAS) comprising 8 electrons in 11 orbitals (3d and 4d orbitals of Fe together with one σ Fe-N orbital). 38 The large (production) active space, CAS (40,42), is equivalent to the active space used in our previous Fe(II)-porphyrin model study, 55 where we have shown that such a large CAS is necessary for quantitatively correct results. This active space contains the 3d, 4s, 4p, and 4d orbitals of Fe, the four σ Fe-N orbitals, and the complete π space of the conjugated porphyrin ring.…”
Section: Computational Detailsmentioning
confidence: 91%